EFFECT OF EASE OF USE AND BENEFITS E-WALLET FOR TRANSACTION IN MSMES EAST TELUKJAMBE DISTRICT KARAWANG - Susanti Nurmalasari; Dedi Mulyadi; Santi Pertiwi Hari Sandi (Jurnal Ekonomi, 2023)
This study aims to determine and analyze the influence of Ease of Use and Benefits variables on E-wallet Transaction Interest in MSMEs, East Telukjambe District, Karawang Regency. This study used a descriptive method with a quantitative approach. The sampling technique used is Purposive sampling and uses the slovin formula so that 100 respondents are obtained. The data analysis technique used is to use path analysis with partial and simultaneous hypothesis testing. The result of this study is that there is a strong and positive correlation between the variables of ease of use and benefits. Partially, ease of use has a positive and significant influence on transaction interest, and benefit variables have a positive and significant influence on transaction interest. And simultaneously the variables of ease of use and benefits have a positive and significant effect on transaction interest.